Half-Sandwich Arene Ruthenium(II) Thiosemicarbazone Complexes: Evaluation of Anticancer Effect on Primary and Metastatic Ovarian Cancer Cell Lines - Guler, Seminay; Kayali, Hulya Ayar; Sadan, Egemen Orkun; Sen, Betul; Subasi, Elif (Frontiers in Pharmacology, 2022)
Herein the synthesis, characterization, and antiproliferative activity of organo-ruthenium(II) half-sandwich complexes [(η6-p-cym)Ru(N,S-L)Cl]Cl (I, II and III), where L= 5-nitro-2-carboxyaldehyde-thiophen-N-methyl-thiosemicarbazone, (L1); 2-acetyl-5-bromo-thiophen-N-methyl-thiosemicarbazone, (L2) and 2-acetyl-5-bromo-thiophen-N,N-dimethyl-thiosemicarbazone, (L3), were reported, respectively. The isolated compounds were analyzed using elemental analysis, FT-IR, 1H NMR spectroscopy, MALDI-TOF mass spectrometry and single-crystal XRD. The spectroscopic studies showed that thiosemicarbazone ligands (TSCs) are coordinated to the central metal as a bidentate ligand coordinating via the thiocarbonyl sulfur and azomethine nitrogen atoms in all complexes (I, II and III). The X-ray crystal structures of L1 and L2 revealed that both compounds crystallized in the triclinic crystal system with space group P-1. Biological potency of newly synthesized TSC ligands (L1, L2 and L3) and their corresponding ruthenium complexes (I, II and III) were investigated on human primary ovarian (A2780) and human metastatic ovarian (OVCAR-3) cell lines. To acquire detailed information regarding antitumor properties, cytotoxicity, DNA/BSA binding affinity, cellular uptake, DNA binding competition, trans-epithelial resistance measurement assays were performed. Our results highlight the impact that newly synthesized ruthenium(II) complexes can have potential biological activity. Moreover, the ruthenium complexes reported here shows anticancer activity aganist primary (A2780) and metastatic (OVCAR-3) ovarian cancer cells.